HIV/AIDS in Latin America : The Challenges Ahead - Garcia-Abreu, Anabela; Noguer, Isabel; Cowgill, Karen (World Bank, Washington, DC, 2013)
Information on HIV/AIDS epidemics in Latin America is disperse and lacks comprehensiveness. Sound and timely policies can limit the current and future impact of the epidemics but good policies are built on a strong epidemiological base and according to the countries' needs. The aim of this study was to assemble all the information available on the epidemiological pattern of the epidemics in Latin America and to gather information on current national surveillance capacity, national responses of the health sector to identify key areas where specific interventions are needed. Through national statistics, data published by international organizations, and databases searches, the authors collected data on the extent, trends and patterns of HIV/AIDS epidemic in 17 Latin American countries. Data on national surveillance systems and national responses from the health sector were gathered through questionnaires applied to managers of the national HIV/AIDS surveillance system, director of the National HIV/AIDS program, NGOs, and physicians. Despite relatively high rates of HIV infection in most countries, many Latin American countries have not yet faced a full-scale AIDS epidemic. HIV/AIDS falls within the framework of a low endemic setting; in the majority of the countries the epidemic is still concentrated in high-risk populations. Latin America has the necessary infrastructure to efficiently and effectively confront the HIV/AIDS epidemic. However, the capacity to respond has been limited by political, technical and social problems. Several key problems on the areas of prevention, access to health and social services, human rights and national capacity were identified. The results of the study suggest that the main challenges to meeting the current needs are (i) availability of resources; (ii) institutional capacity to provide training in all areas; and (iii) cultural, social and religious factors.